The future of the ecological farm: Ten opinions and evaluations. Results of applying Delphi method - Violeta Florian; Mihai Alexandr Chiţea; Marioara Rusu; Ioan Sebastian Brumă; Lucian Tanasǎ (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
If we can decipher the content of opinions and evaluations of those involved in ecological agriculture then we could know the subjective fundamentals/resorts of the modernization and ecological development's process at the level of the rural communities. The study mainly aims at identifying the opinions on the ecological farm's evolutions, and, as general objectives: knowing the projections regarding employment in ecological farm, employment in agriculture's support services, determining the way in which the consequences of using ecological practices on the supply chain and impact on rural communities are perceived. The scientific approach on the ecological subjectivity has turned to a structured communication method, Delphi, in three stages. The study was implemented in a rural area defined by concernments and ecological agricultural activities - Dornelor Basin, Suceava county and it has identified the content, persistence, flexibility and statements' meaning (positive/negative) of opinions regarding the future of the ecological farms.
Keywords: Q01; Q57; 330; ecological farm; opinion; evaluation; Delphi method